Modern Technology inLifting Waste andModern Waste Containers and Their Spread intheCity of Baghdad / Case Study (Journal of the College of Basic Education, 2020)
The problem of waste occupies the interests of the developed countries and prepares strategic plans with timetables that keep abreast of the development, population growth, industrialization, reconstruction, and expansion. The developing countries, including most of the Arab countries, have limited interests including Iraq. Some municipal departments used modern waste containers (The ground) Within the scope of the provision of services by them, But it was not successful in the selection of the distribution of containers and their number and this is what we found in the research as well as the use of modern technology in the lifting of waste through the computer and reduce labor.